Recurrence of vulvar carcinoma: A multidisciplinary approach - M. Rei; R. Mota; V. Paiva; A. Duarte; J. Costa; A. Costa (Elsevier, 2019)
Although oncogynaecological management of bulky vulvar tumors tends to minimally-invasive approaches preceded by neoadjuvant therapies, ultra-radical surgery with curative intent may still have an important role. These procedures remain associated with significant short and long-term complications, imposing the need for novel reconstructive techniques [1-4].We present a video highlighting the crucial surgical steps of a successful pelvic exenterative procedure followed by perineal reconstruction with a muscle-sparing flap technique.A 72-year woman with history of stage II vulvar epidermoid carcinoma, treated with radical surgery and adjuvant radiotherapy. At two-year follow-up local recurrence was diagnosed, handled with large excisional surgical treatment. Within four years a second local recurrence occurred, with infiltrative and bulky dimensions extending to perianal region and vaginal wall.A multidisciplinary surgical approach with curative intent was performed, involving gynecologists, colorectal and plastic surgeons: radical bilateral vulvectomy with distal colpectomy, abdominoperineal resection with colostomy, perineal reconstruction with deep inferior epigastric perforators (DIEP) flap. No major intraoperative or postoperative complications occurred, and the patient was discharged within two weeks with no readmissions for wound care. At two-year follow up she remains in complete remission of the disease. No flap complications occurred during this period.In highly selected patients with recurrent vulvar cancer previously submitted to multiple surgeries and radiotherapy, pelvic exenterative procedures followed by reconstructive techniques allow free surgical margins minimizing morbidity and pelvic disfiguring surgery. Association of reconstructive techniques to radical vulvo-vaginal surgery can shift the paradigm of oncological treatment approach, improving outcomes and quality-of-life. Keywords: Vulvar cancer, Recurrence, Pelvic exenteration, Reconstruction